Effects of Technological Conditions on Preparation of Metal Zr Using Electro-Deoxidation Method in CaCl2-NaCl Molten Salt - WANG You-qun1，2; LIN Ru-shan; HE Hui; WANG Huan; LIU Yun-hai (He huaxue yu fangshe huaxue, 2022)
The conversion of oxides into metals is one of the key steps in the dry reprocessing of spent oxide fuel using the molten salt electrorefining method. In this study, in the CaCl2-NaCl molten salt system, graphite rods were used as anodes, and the high-temperature sintered ZrO2 flakes were simulated UO2 cathode. Besides, the FFC Cambridge process conditions of electro-deoxidation to prepare metal zirconium in CaCl2-NaCl molten salt were optimized. The effects of electrolysis process conditions(cell voltage, electrolysis time, sintering temperature, and electrolysis temperature, etc.) on the preparation of Zr by electro-deoxidation was studied systematically. SEM and XRD were utilized to analyze the microstructure and phase composition of the ZrO2 cathode before and after electrolysis, respectively. The optimized process conditions are voltage of 3.4 V, electrolysis time of 12 h, sintering temperature of 900 ℃, and electrolysis temperature of 722 ℃. At the same time, the intermediate products CaZrO3 and ZrO are found in the conversion of ZrO2 into Zr.